Integrated online Delta beverages acquisition System - Chimbwanda, Tambirai Blessed (Midlands State University, 2018)
The purpose of the project entitled “Integrated Online Delta Beverages Acquisition system” was to help Delta Beverages in offering its clients an outstanding service and also paying attention to the health of the business and that of the clients. The system was also meant to offer unswerving, faster and efficient means to assist Delta clients in getting better assistance than what the current system has been offering. Henceforth, the system provided a booking facility such that the client just has to log into Delta account and order for the products he or she wishes to purchase without physically attending to the organization’s premises. A feasibility study was performed to check whether the new system was feasible in all aspects (that is socially, economically, technically and operationally) to undertake. The researcher used different research methodologies that are interviews, questionnaires, observations and decision groups to confirm the operations of the old system and check the need of a new system. The findings indicated the need to develop a new system thus, the developer went on to develop the system which have been implemented. The documentation thus involved the proposal, planning, analysis, system design and system implementation phases.